Effects of Logging on Streamwater Quality and Solute Input-Output Budgets in Small Watersheds in Peninsular Malaysia - Yusop, Zulkifli (1990)
The effects of selective logging on streamwater quality and solute budget s were investigated using three small catchments: C1, C2 and C3. After a three-year calibration period,Cl and C3 were logged using" unsupervised" and "supervised" logging methods respectively, whereas C2 was left as control. Several control measures were imposed in the supervised C3 but none in the unsupervised C1. During the calibration period the levels for most of the streamwater quality parameters measured were within the standards for potable water. The exceptions were colour, turbidity and iron.Significant increases in pH, specific electrical conductivity, hardness, suspended solids, alkalinity, turbidity, dissolved solids, silicate, calcium, iron,and sodium were recorded in the unsupervised C1. The levels for colour and nitrate were also elevated initially but recovered to background values within a year. In contrast, in the supervised C3, significant changes were detected only for hardness, magnesium and iron. The impact of logging was enhanced during the wet months especially for suspended solids, turbidity and iron.